Impact of hydroxychloroquine on preterm delivery and intrauterine growth restriction in pregnant women with systemic lupus erythematosus: a descriptive cohort study. (November 2015) - Leroux, M; Desveaux, C; Parcevaux, M; Julliac, B; Gouyon, J-B; Dallay, D; Pellegrin, J-L; Boukerrou, M; Blanco, P; Lazaro, E
Objective: The aim of this study was to evaluate the effect of hydroxychloroquine (HCQ) on fetal preterm delivery and intrauterine growth restriction (IUGR) in a cohort of pregnant women with systemic lupus erythematosus (SLE). Methods: Over an 11-year period (January 1, 2001 to December 31, 2011), all women with SLE and admitted to deliver after 22 weeks of gestation to Bordeaux University Hospital (France), were retrospectively enrolled in the present study. The population was then split into two groups based on the treatment they received: HCQ exposed (HCQ+) versus HCQ non-exposed (HCQ−) group. Results: 118 pregnancies were included, 41 in the HCQ+ group and 77 in the HCQ− group. The rate of adverse fetal outcome was significantly lower in the HCQ+ group ( p  = 0.001), particularly in terms of preterm delivery, 15.8 % versus 44.2 % ( p  = 0.006), and IUGR, 10.5 % versus 28.6 % ( p  = 0.03). No adverse outcomes were reported in the HCQ+ group. Conclusion: HCQ reduces neonatal morbidity in women with SLE by significantly decreasing the rate of prematurity and intrauterine growth restriction.